2017
DOI: 10.1115/1.4037615
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization of Human Operations in the Age of Cyber Manufacturing: Sensorimotor Analysis of Manual Grinding Performance

Abstract: This paper presents new techniques to analyze and understand the sensorimotor characteristics of manual operations such as grinding, and links their influence on process performance. A grinding task, though simple, requires the practitioner to combine elements from the large repertoire of his or her skillset. Based on the joint gaze, force, and velocity data collected from a series of manual grinding experiments, we have compared operators with different levels of experience and quantitatively described charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Economic growth and job creation vary depending on the level of technological development of a country [17]. Other researchers [18][19][20] stated that employees in the service sector have a great role in increasing the rate of profit, which is the main purpose of the enterprises, to run the business smoothly, and to ensure customer satisfaction and loyalty. Digitization is one of the most visible phenomena of this decade, and its evolution is extremely fast.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Economic growth and job creation vary depending on the level of technological development of a country [17]. Other researchers [18][19][20] stated that employees in the service sector have a great role in increasing the rate of profit, which is the main purpose of the enterprises, to run the business smoothly, and to ensure customer satisfaction and loyalty. Digitization is one of the most visible phenomena of this decade, and its evolution is extremely fast.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the process of manual grinding, as opposed to automated grinding, depends on the knowledge, skills, posture, gripping forces, and personal strength of the user [13]. This means that the user influences the grinding tangential force and grinding normal force, hence the consistency of the whole grinding process [14]. In addition, the grinding forces are influenced by grinding disc wear and manual feed [1].…”
Section: Introductionmentioning
confidence: 99%
“…A skilled operator is expected to be highly adaptable, flexible, and able to quickly learn from process changes. Studies have shown that skills involved in these manual tasks are largely procedural rather than declarative, meaning that they are self-regulatory and orchestrated by an individual operator [3,4]. Surprisingly, even though manual abrasive operations have a growing market, they are under-researched, and limited work has been done on manual process parameters and their effect on surface integrity.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed investigation of the interrelationship between skill level and process performance can quantify the intricate behavioral complexity involved in manual operations. It can be anticipated that for manual operations, machining process parameters are largely dependent on humanmachine interactions [4] and can greatly influence product outcome [5,6]. To make this humanmachine interaction more effective, there is a need for a quantified, formal method of measuring, representing, transferring, and reasoning about human skills in order to (i) efficiently allocate resources and tasks among humans, between humans and machines, and cross-factories, (ii) expand and enhance human capabilities, and (iii) optimize system behavior to predict the product performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation